Nanoparticle Technology for Development of Immunostimulant Drugs Using Natural Product : Narrative Review - Seran, Yuvina (Indonesian Journal of Pharmaceutical Science and Technology, 2025)
The field of nanotechnology focuses on systems at the nanometer scale. Nanotechnology is used in the medical field for drug development, medical imaging, and gene therapy. One application of nanotechnology is nanoparticles. Nanoparticles have sizes in the nanometer range, with a scale of 1 to 100 nm. Nanoparticles can be designed to stimulate the immune system and improve the immune response. Literature study using research articles from national and international journals the application Publish or Perish 8 based on the keywords "Immunostimulants, Nanotechnology, nanoparticle, gold nanoparticle, and silver nanoparticle." Based on searching various literature studies, it is proven that nanoparticle preparations can increase immunostimulants with various testing instruments that are often found, namely FTIR (Fourier Transform Infrared), WHICH (Scanning Electron Microscopy), XRD (X-ray Diffraction), HE HAS (Transmission Electron Microscopy), particle size, zeta potential, and spectroscopy UV-visible. Nanoparticles can be an effective drug delivery system and can help maintain the immune system in the body.